Vai trò của các yếu tố cá nhân và bối cảnh công việc trong hình thành ý định khởi sự kinh doanh kết hợp - Nguyễn Tuấn , Tài; Dương Công , Doanh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The objective of the study is to explore the role of individual factors and work-context factors in shaping hybrid entrepreneurial intention. Through structural equation modeling analysis with 284 observations, the results indicate that self-efficacy in managing conflict between work and a private business project is the strongest influencing factor. The study also finds the moderating role of polychronicity on the relationship between self-efficacy and hybrid entrepreneurial intention. From a theoretical perspective, the research successfully explains hybrid entrepreneurial intention, clearly identifying which type of self-efficacy is key. The study tested the moderating role of a personality factor – which is rarely examined in studies applying social cognitive career theory. From a practical perspective, the results suggest the type of personal competence needed for hybrid entrepreneurship and emphasize the role of leadership style in the career development of employees